Implementasi Ketentuan Tentang Wilayah Berdagang Bagi Pedagang Kaki Lima di Kota Bandung - A. Aris Swantoro; Tisa Windayani (Jurnal Perkotaan, 2016)
In many cities in Indonesia street vendors have given a quite significant contribution to the local’s economy. However, their physical existence oftenly gives an undesirable impact to the area itself. Aligned with the concept of regional autonomy which is regulated in the Law No 32/2004 concerning the Regional Autonomy, which was later revised by the Law N0 23/2014, provincial government has the rights as well as responsibilities to manage some of the governmental matters. The authority of Kota Bandung had issued the Regional Law No. 4/2011 concerning the management of street vendors. One of the essential matters in the respected law is the categorization of the areas for vending into three zones. One of those is the red zone, within which vendors are not allowed to exist physically, nor to have business activities. Nevertheless the law aims to accommodate as well as to manage street vendors, so that they could positively contribute to the city. This research examined whether or not law is properly implemented. It is found that the efforts to accommodate the vendors from the authorities have not been carried out optimally. The only attempt to enforce the law concerning the red zone is the repressive kind, with no permanent results of discontinuity from the part of the vendors to operate their business some time after. Almost all of the vendors interviewed stated that they had never been engaged in any form of efforts from the local government.